TI_GERICHTE 12.2005.5 vom 11. August 2005 , spese legali preprocessuali - ripetibili - assistenza giudiziaria - TI Tribunale d'appello (2005)
spese legali preprocessuali - ripetibili - assistenza giudiziaria